Zeofen as a Catalyst for Cleavage of Semicarbazones and Phenyl Hydrazones Under Conventional Heating and Microwave Irradiation - HEKMATSHOAR, RAHIM; JAVANSHIR, SHAHRZAD; A. OSKOOIEE, HOSSEIN; M. HERAVI, MAJID (Asian Journal of Chemistry, 2010)
Semicarbazones and phenylhydrazones are oxidatively cleaved under conventional heating and microwave irradiation in solventless system to generate the corresponding carbonyl compounds by zeofen as catalyst.